Peningkatan Budaya Literasi melalui Pelatihan Menulis Cerita Pendek pada Siswa MAN 1 Brebes - Ratri Wikaningtyas; Dany Sucipto; Qirom Qirom; Rozin Arkan; Putri Izza; Ulil Albab; Bahrun Niam (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2025)
This Community Service Program (PKM) aims to enhance literacy culture among students through a short story writing workshop conducted at MAN 1 Brebes. The program was initiated in response to the low interest in reading and writing among teenagers. The training was carried out intensively using a project-based learning approach, emphasizing the creative writing process from planning and drafting to revision. Participants were encouraged to choose their own story themes to foster personal and emotional engagement in writing. Evaluation was conducted through pretests and posttests to measure improvement in writing skills. The results showed that 87% of participants experienced an increase in scores, particularly in understanding story structure, diction usage, and conflict development. Each student produced one short story, which was compiled into a digital anthology as the final product of the training. This activity proved effective in fostering literacy interest and improving students' writing abilities, and it is expected to serve as a model for similar training programs in other educational settings.